PATTERN OF CUTANEOUS WOUND HEALING IN A IVE l ISH CLARIAS BATRACHUS (L.) (CLARIIDAE, PISCES.) - DUTTA, M.; RAJ, A. K. (Journal of Indian Fisheries Association, 2015)
Incisional wounds of the same lengih and depth. were made on sldn between dorsal fin and the lateral line canal of Clarias batrachus and the pattern of wound closure has been studied histologically. Following infliction, a marked change in the colour of the skin surrounding the wound was observed which lasted for about 30 h and. restored thereafter. Mucus and blood cells plugged the wound gap shortly after infliction. The . epidenuis surrounding the wound was Â·found to be detached from the basement membrane. !movement of epidermal cells was observed from both side of the wound gap. The epidermal cells at the margin of the wound became hypertrophized. The epidernlis beca.Ine normal by 32 days. The dealing of subepidermal tissue indicated degenerative and Â·regenerative changes of muscle fibres. The mucus and blood cells were accumulated in the wound gap and later fine blood vessels. were forxned. Gradually granulation tissue was formed and fibroblasts and myoblasts appeared. Myoblast differentiated into muscle bundles. The epidermal repair was completed within 85 days.